Gerência de operações em cooperativas agropecuárias: fatores produtivos estruturais relevantes para o desempenho econômico-financeiro - Martins, Fellipe Silva (2013)
Studies on performance of agribusiness cooperatives in Brazil focus on their economic and financial aspects. This study aims to further delve into such studies by investigating which commonly measurable structural productive factors (horizontal, vertical and lateral diversification; operating area; number of associates; and operating time) have greater impact on the financial performance of such cooperatives. To achieve such a goal, a survey was conducted with the sampling pool divided by size (annual gross revenues of R$ 50 million or higher) and employing the questionnaire as a method of data collection. The sample was concentrated in the South, Southeast and Midwest regions of Brazil, segregated by size and deemed adequate after several adequacy tests. The results were analysed using Spearman correlation which allowed understanding that there were no significant correlations between the structural productive factors considered in the study and the economic-financial performance of agricultural cooperatives in isolation, which leads to questioning about the effectiveness of employing diversification strategies out of a conjoint approach. Nonetheless, it was possible to identify several relationships not contemplated in the original hypotheses that might be further addressed in future studies. On the other hand, by creating an overall performance variable, and applying cluster and discriminant analysis, it was established the existence of two groups of cooperatives with distinct behaviours: whereas one group makes minimal use of the studied structural factors and achieve average performance, the other makes intensive use of these and obtain a considerably better performance. Finally, by means of the Fischer discriminant function it was possible to correctly classify all the cooperatives (with 0% of types I and II errors) in both groups in relation to their economical-financial performance.